Mutual illumination - Forsyth, D; Zisserman, A (IEEE, 1989)
The authors report theoretical and experimental results which underline the importance of mutual illumination to visual modules dealing with shape and with surface lightness. The experiments are in good agreement with results obtained with a simple theoretical model. These results show the effects of mutual illumination in pictures of simple objects, and indicate that these effects must be accounted for in modeling image intensities. The data imply that shape from shading based on the image irradiance equation make real errors on images of concave objects, and that edge detectors that respond to only step edges perform badly on polyhedral scenes and waste information.